Non-Heat Treatable Al-Alloys: Development of Intermetallic Particles during Solidification and Homogenization - Engler, Olaf; Kuhnke, Katrin; Hasenclever, Jochen (CRC PRESS-TAYLOR & FRANCIS GROUP, 2019)
The materials properties of Al-alloys are controlled by the added alloying elements and by the processing conditions through the resulting materials microstructure.An important aspect in the description of the microstructure is the constitution of the material in terms of alloying elements in solid solution and, in turn, volume, size, morphology, and species of second-phase particles.These constitutional characteristics, conveniently summarized as microchemistry, have an impact on physical properties like thermal or electrical conductivity and on mechanical properties including strength and formability of Al-alloys.In the present article, we summarize the phase selection upon solidification and the changes in microchemistry during subsequent homogenization-annealing during conventional industrial processing of non-heat-treatable Al wrought alloys.
Keywords: Homogenization; Microchemistry; Precipitation; Solidification; Solutes; Wrought alloys; CAST AA3003 ALLOY; ALUMINUM-ALLOY; MG ALLOYS; COOLING RATE; PRECIPITATION KINETICS; THERMOELECTRIC-POWER; 2ND-PHASE PARTICLES; ALFESI-PARTICLES; HOT WORKABILITY; PHASE SELECTION; Materials Science; Metallurgy & Metallurgical Engineering